Perspektif Guru dalam Penggunaan Model Inkuiri Terhadap Literasi Sains Siswa di Kelas Tinggi - Widianti, Almaidah; Jayadinata, Asep Kurnia; Sudin, Ali (Jurnal Pena Ilmiah, 2021)
This research is become to know about teacher’s perspective especially on the students science literacy. In this century, science literacy is a must skills they had. Inquiry models can help to increase that skills. Process in the inquiry make the students as centre through scientific activities thru finding an answer for the solution the problems  of the learning independently. Therefore, the research was carried out the aims to know about inquiry model in science learning, to know students’ sciencse literacy and the effect of inquiry models for science literacy based on teacher perspective. A method for this research is quantitative descriptive and survey as the research design. High grades primary teacher at  Dukupuntang district become the population. Proportional sampling is used to this research. The instument is questionnaire. The implication is inquiry could intensify science literacy because it can make the people compete in the mass of technology.